2004
DOI: 10.3201/eid1006.030660
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposure and Leptospirosis, Peru

Abstract: Human infection by leptospires has highly variable clinical manifestations, which range from subclinical infection to fulminant disease. We conducted a population-based, cross-sectional seroepidemiologic study in Peru to determine potential relationships of environmental context to human exposure to Leptospira and disease associated with seroconversion. Three areas were studied: a flooded, urban slum in the Peruvian Amazon city of Iquitos; rural, peri-Iquitos villages; and a desert shantytown near Lima. Seropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
119
1
23

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(153 citation statements)
references
References 29 publications
(30 reference statements)
10
119
1
23
Order By: Relevance
“…The highest seroprevalence (19%) was reported for people living in SES-1, suggesting an endemic leptospirosis pattern in that zone. The older age group showed the highest Leptospira seroprevalence (18.9%), as described in previous studies, likely due to longer lifetime exposure 9,18,19,20 .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The highest seroprevalence (19%) was reported for people living in SES-1, suggesting an endemic leptospirosis pattern in that zone. The older age group showed the highest Leptospira seroprevalence (18.9%), as described in previous studies, likely due to longer lifetime exposure 9,18,19,20 .…”
Section: Discussionsupporting
confidence: 82%
“…Walking barefoot indoors or outdoors was not significantly associated with the presence of leptospiral antibodies in the study by Ferro et al 9 , but it has been reported as a risk factor elsewhere 20,40,41 . Interestingly, one study from Rural Durango, Mexico found that Leptospira exposure was positively associated with history of domestic travel in the general population 19 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Dentre estas, os equinos são considerados importantes reservatórios devido sua proximidade com os seres humanos, principalmente quando as duas espécies compartilham um ambiente de condições estruturais e sanitárias inadequadas (Johnson et al, 2004;Hamond et al, 2012).…”
Section: Introductionunclassified